Pragmatic characteristics of rhetorical questions arising under the influence of spoken discourse in English and Uzbek - Usmonova, Zarina Habibovna; Nurillayeva, Mavluda Muzaffar qizi; Raximova, Nargiza Maksudovna (The Lingua Spectrum, 2026)
This article explores the pragmatic characteristics of rhetorical questions in English and Uzbek spoken discourse, with particular attention to their functions in conversational language use. Adopting a qualitative comparative approach grounded in pragmatics and discourse analysis, the study examines how rhetorical questions operate beyond their literal interrogative form. The findings demonstrate that such questions are not primarily used to seek information but to perform various pragmatic functions, including emphasis, evaluation, persuasion, and the expression of emotions. Their interpretation is shown to depend heavily on context, intonation, and shared background knowledge between speakers. Although English and Uzbek rhetorical questions exhibit similar communicative purposes, notable differences exist in their structural realization. English tends to employ modal verbs and auxiliary constructions, whereas Uzbek relies more on intonation patterns and contextual cues. The study concludes that rhetorical questions play a significant role in shaping meaning in spoken discourse and reflect the dynamic relationship between language, context, and speaker intention.